2014
DOI: 10.1016/j.cub.2014.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Origins of Developmental Reproducibility

Abstract: Summary Cell fate decisions during multicellular development are precisely coordinated, leading to highly reproducible macroscopic structural outcomes [1–3]. The origins of this reproducibility are found at the molecular level during the earliest stages of development, when patterns of morphogen molecules emerge reproducibly [4, 5]. However, while the initial conditions for these early stages are determined by the female during oogenesis, it is unknown whether reproducibility is perpetuated from oogenesis or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 49 publications
(116 reference statements)
4
37
0
Order By: Relevance
“…While such a scheme involving an intermediary maternal mRNA and protein appears wasteful at first glance, here we have shown that it may provide a substantial benefit for information transmission at low input concentration, i.e., in posterior regions of the embryo. Although we are not familiar with any direct measurement of caudal mRNA copy numbers, the copy numbers for the gap genes [79] (and also bicoid [88]) are consistent with the range M ~ 10 2 -10 3 mRNA per nuclear volume.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…While such a scheme involving an intermediary maternal mRNA and protein appears wasteful at first glance, here we have shown that it may provide a substantial benefit for information transmission at low input concentration, i.e., in posterior regions of the embryo. Although we are not familiar with any direct measurement of caudal mRNA copy numbers, the copy numbers for the gap genes [79] (and also bicoid [88]) are consistent with the range M ~ 10 2 -10 3 mRNA per nuclear volume.…”
Section: Discussionmentioning
confidence: 96%
“…There, each mRNA harbors a binding site of size c ~ 1-10 nm, but the mRNAs typically are separated by distances d ~ 1-10 μm. Roughly, we can expect that input readouts will be independent and the ITR mechanism effective so long as M ≲ d/ c ~ 10 2 -10 4 , putting M in the range that we examined and where it appears biologically plausible; recent experiments in the Drosophila and zebrafish embryos and in mammalian cells reported mRNA counts in the range 50-1200 per typical cell volume [79,[87][88][89][90][91]. For such values of M, we find significant increases in capacity of 0.8-1.8 bits at C ~ 0.1-1, with optimal regulatory curves using high…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have quantified the number of transcripts for two genes included in this study, using FISH to estimate the number of transcripts (Boettiger and Levine 2013;Petkova et al 2014). One study of bcd transcripts prior to the syncytial blastoderm stage and NC10 found 890,000 transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…The direct detection of messenger RNA (mRNA) molecules minimizes steps between sample collection and data acquisition, reducing error, sample loss, or contamination. RNA-seq has been used in past studies of the Drosophila MZT to quantify the number of transcripts for a gene in the early embryo, and while these studies provide an abundance of data for all genes transcribed, the methods used have been shown to introduce bias in transcript count and read coverage that can hamper absolute quantification of transcripts (Hansen et al 2010;Lott et al 2011;Roberts et al 2011;AliMurthy et al 2013;Petkova et al 2014).…”
mentioning
confidence: 99%
“…a single cell. Indeed, a similar situation has been observed in the early embryo where the precision of molecular patterns that are set up during oogenesis lead to precise molecular patterns in the early embryo all the way to the first macroscopic pattern, the cephalic furrow [12,14,36,37]. This connection between the early embryo and the final adult wing structure indicates that spatial reproducibility of morphogenetic features in the fly may be maintained throughout the entire 10 days of development.…”
Section: Discussionmentioning
confidence: 68%